CONNAISSANCES, ATTITUDES ET PRATIQUES DES ELEVES FILLES DES ECOLES SECONDAIRES DE LUBAO FACE AUX INFECTIONS SEXUELLEMENT TRANSMISSIBLES - Kapenga Ntambwe Senghor (IJRDO - Journal of Social Science and Humanities Research, 2024)
This reflection, which is part of the field of health psychology, assesses, through surveys and documentary research, the level of information relating to health problems and behaviors of female students attending school in the extra-customary city of Lubao, in the Republic Democratic Republic of Congo in the face of sexually transmitted infections. It aims to understand the links between psychological factors, health and illness in the school environment. Regarding practices, she seeks to show that for the most part, the behavior of most female students is closely linked to certain socio-cultural realities including the precocity of sexual initiation; low risk perception; the deficit in sex education at school and in families; insufficient knowledge about sexually transmitted infections; the absence of means of protection; poverty ; the disappearance of values ​​and the low use of condoms. Behind this problem which concerns several educational partners, she expresses the opinion that it is important to look at the contents of training programs linked to life education deemed compatible with socio-cultural imperatives or which constitute obstacles to academic success and attempts to suggest responses in terms of promoting school health.